Elaboração de um catálogo de espécies de peixes com ocorrência no estuário do rio Vaza-Barris, Sergipe - Amor Divino, Camilo Emmanuel Viana (2015)
Little is known about the composition, abundance and structure of the ichthyofauna. Regarding the estuary of the Vaza-Barris River, it is necessary to conduct a systematized monitoring of this ecosystem with regard to the survey and the dynamics of the occurrence of fish, providing subsidies for the understanding of the use of these areas by the community and for the implementation of possible management plans. The lack of information about the marine and estuarine ichthyofauna of the State of Sergipe refers to the need to create a data bank and a visual collection of the species that occur in these ecosystems. The work plan aimed to create an informational-visual collection of the species captured in the estuary of the Vaza-Barris River during a year of ichthyofaunistic sampling carried out along the whole estuarine system, from its lower portion to its upper portion. Thus, this study unprecedentedly sought to follow up on the estuarine system of the Vaza-Barris River, cataloging the species of fish that live in this habitat, storing and making available data that allow better information for management, whether fishing, tourism programs or even to support public policies for environmental preservation. The results show that one hundred species were captured, distributed fifteen orders, forty-one families and seventy genera